Measuring the Impact of Equity Promotion Policies - Salmi, Jamil (International Higher Education, 2020)
This article analyzes five case studies of what works in equity: Australia, Austria, Colombia, South Africa, and Vietnam. The studies confirm that achieving strong equity results requires a high degree of alignment among leadership, policy goals, policy instruments, and resources. They also show the interaction of structural elements influencing disparities in higher education: streaming within high schools, selectivity in university admissions, institutional differentiation of higher education systems, and availability of financial aid for disadvantaged groups.